Effect of legume and grazing intensity on soil organic carbon and total nitrogen stock in Himalayan rangeland - Limbu, Dil Kumar; Koirala, Madan; Shang, Zhanhuan (Our Nature, 2019)
Organic carbon and total nitrogen are important components of global carbon and nitrogen cycle in rangeland ecology.Objective of this study is to identify and quantify the present status of carbon and nitrogen pool in Himalayan rangeland and to make recommendations for enhancing carbon and nitrogen storage for rangeland management. To meet the aforementioned objectives, the field study was conducted in 2011 -2013. The study showed that soil organic carbon was highest in legume seeding sub-plot in top soil (28.53 ± 2.6) t/ha of heavily grazed area. Similarly, total nitrogen was highest in bottom soil (2.81 ± 0.16) t/ha in legume seeding sub-plot of enclosed un-grazed area. Usually, heavily grazed and legume seeding sub-plots had more soil organic carbon and total nitrogen concentration compared to others. The value of above ground biomass was in increasing trend with decreasing grazing intensity but for below ground biomass, it was just the reverse. On the basis of the results of this study, the grazing intensity is positively correlated with above ground and below ground biomass and soil organic carbon but no correlation with soil total nitrogen and soil bulk density.